2020
DOI: 10.1038/s41598-020-72371-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic effects of hydrogen sulfide suppress soluble Flt-1 and soluble endoglin in cystathionine gamma-lyase compromised endothelial cells

Abstract: Endothelial dysfunction is a hallmark of preeclampsia, a life-threatening complication of pregnancy characterised by hypertension and elevated soluble Fms-Like Tyrosine Kinase-1 (sFlt-1). Dysregulation of hydrogen sulfide (H2S) by inhibition of cystathionine γ-lyase (CSE) increases sFlt-1 and soluble endoglin (sEng) release. We explored whether compromise in CSE/H2S pathway is linked to dysregulation of the mitochondrial bioenergetics and oxidative status. We investigated whether these effects were linked to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
(98 reference statements)
1
10
0
Order By: Relevance
“…In conclusion, the development of this refined surgically induced model of preeclampsia that captures major preeclampsia features including up-regulation of sFlt-1 and down-regulation of protective enzymes offers a unique opportunity to test novel therapeutics for the prevention of preeclampsia. MZe786 significantly limited the development of preeclampsia in the mRUPP model by suppressing sFlt-1 and nitrosative stress as well as improving antioxidant genes [ 21 ] and cellular mitochondrial function [ 64 , 65 ]. This compound warrants urgent investigation in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the development of this refined surgically induced model of preeclampsia that captures major preeclampsia features including up-regulation of sFlt-1 and down-regulation of protective enzymes offers a unique opportunity to test novel therapeutics for the prevention of preeclampsia. MZe786 significantly limited the development of preeclampsia in the mRUPP model by suppressing sFlt-1 and nitrosative stress as well as improving antioxidant genes [ 21 ] and cellular mitochondrial function [ 64 , 65 ]. This compound warrants urgent investigation in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of H 2 S donors has been recognised as a potential approach to modulate cellular bioenergetics and ATP production in a myriad of adverse pathological conditions [ 37 , 42 , 43 , 44 , 45 , 46 ]. Furthermore, as others have previously reported, under hypoxia, cells fail to activate mitochondrial respiration, relying primarily on glycolysis for energy supply [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following, to evaluate mitochondrial and glycolytic function, a set of drugs/inhibitors: oligomycin (O) (1 mM) (Sigma-Aldrich, Dorset, UK), carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP) (0.5 mM) (Sigma-Aldrich, Dorset, UK), 2 deoxy glucose (2-DG) (Sigma-Aldrich, Dorset, UK) and a mixture of rotenone and antimycin A (Rot/AntA) (1 mM) (Cayman Chemicals, Michigan, USA) were injected sequentially, using available ports to: inhibit the ATP synthase, uncouple oxidative phosphorylation, inhibit glycolysis and estimate non-mitochondrial respiration, respectively. From OCR readings, this experiment measures six parameters of the mitochondrial function: basal oxygen consumption, ATP-linked oxygen consumption, proton leak, maximal oxygen consumption, reserve capacity, and non-mitochondrial oxygen consumption as we have previously optimised [ 37 , 38 , 39 ] ( Supplementary Figure S1A ). From ECAR readings, the experiment allowed to calculate three glycolysis related parameters: basal glycolysis, glycolytic capacity and glycolytic dependence ( Supplementary Figure S1B ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, a recent study demonstrated that suppression of CSE in human umbilical vein endothelial cells (HUVECs) results in mitochondria dysfunction by elevating the expression of soluble anti-angiogenic markers, fms-like tyrosine kinase-1 and endoglins, whereas supplementation of H 2 S by the donor AP39 could reverse the effect and improve cellular bioenergetics and reactive oxygen species (ROS) levels [ 72 ]. The treatment of HUVECs with a hybrid H 2 S and NO donor, ZYZ-803, has also been demonstrated to promote angiogenic properties by activating the signal of transducer and activator of transcription 3 (STAT-3)/Ca 2+ /calmodulin-dependent protein kinase II signaling cascade [ 73 ].…”
Section: Role Of H 2 S In Vascular Functionmentioning
confidence: 99%